ARTIFICIAL INTELLIGENCE AND BIG DATA IN EDUCATION: SHAPING THE FUTURE OF LEARNING AND TEACHING (Web of Discoveries: Journal of Analysis and Inventions, 2024)
The use of Artificial Intelligence and Big Data in education has great potential to improve the quality of teaching and learning management. It is used to personalize the learning process, improve student outcomes, and optimize administrative tasks. It is capable of analyzing student's learning style and customizing educational content according to their individual needs. By collecting and analyzing large amounts of data, valuable insights into learning processes and student needs can be gained, allowing for a more efficient learning process and personalization of learning. However, when using Big Data in education, high standards of data protection and ethical principles must be observed.